Political Interference in Election Administration and Electoral Irregularities in Nigeria - Uchenna C. Obiagu; Peter O. Mbah; Chikodiri Nwangwu; Ikenna Martins Ibekwe; Clarence Odey; Felix Onen Eteng (Modern Africa, 2025)
The extant literature is replete with fine-grained explanations of problems of electoral irregularities in Nigeria. However, how political interference in election administration contributes to these problems has largely remained unacknowledged. The Nigerian Constitution establishes the Independent National Electoral Commission (INEC) as a relatively autonomous electoral body and, also, empowers the president to appoint its principal officers subject to Senate confirmation. These provisions that allow interested parties to determine INEC membership composition delink INEC’s institutional design from its operational independence and, therefore, incapacitate it from asserting its independence in order to guarantee credible elections in Nigeria. The present study relies on a triangulation of qualitative research techniques such as documentary sources, key informant interviews, and personal observations. Premised on descriptive statistics and content analyses, this study reveals that political interference in INEC membership composition and financing considerably accounts for recurring lethal electoral irregularities; shows that whoever controls the human and financial elements of INEC is in firm control of its operations for favourable electoral outcomes; and suggests the need for voter-determined reforms for a workable electoral system in the context and content of Nigeria.